Aquaponic and Hydroponic Solutions Modulate NaCl-Induced Stress in Drug-Type Cannabis sativa L. - Yep, Brandon; Gale, Nigel V.; Zheng, Youbin (Frontiers in Plant Science, 2020)
The effects of salt-induced stress in drug-type Cannabis sativa L. (C. sativa), a crop with increasing global importance, are almost entirely unknown. In an indoor controlled factorial experiment involving a type-II chemovar (i.e., one which produces Δ9-tetrahydrocannabinolic acid ~THCA and cannabidiolic acid ~ CBDA), the effects of increasing NaCl concentrations (1 – 40 mM) was tested in hydroponic and aquaponic solutions during the flowering stage. Growth parameters (height, canopy volume), plant physiology (chlorophyll content, leaf-gas exchange, chlorophyll fluorescence and water use efficiency), and solution physicochemical properties (pH, EC and nutrients) was measured throughout the experiment. Upon maturation of inflorescences, plants were harvested and yield (dry inflorescence biomass) and inflorescence potency (mass-based concentration of cannabinoids) was determined. It was found that cannabinoids decreased linearly with increasing NaCl concentration: -0.026% and -0.037% THCA·mM NaCl-1 for aquaponic and hydroponic solutions, respectively. The growth and physiological responses to NaCl in hydroponic – but not the aquaponic solution – became negatively affected at 40 mM. The mechanisms of aquaponic solution which allow this potential enhanced NaCl tolerance is worthy of future investigation. Commercial cultivation involving the use of hydroponic solution should carefully monitor NaCl concentrations, so that they do not exceed the phytotoxic concentration of 40 mM found here; and are aware that NaCl in excess of 5 mM may decrease yield and potency. Additional research investigating cultivar- and rootzone-specific responses to salt-induced stress is needed.